B cells contribute to MS pathogenesis through antibody-dependent and antibody-independent mechanisms - Wilson HL (Dove Medical Press, 2012)
Heather L Wilson1,21Vaccine and Infectious Disease Organization-International Vaccine Center, 2Department of Biochemistry, University of Saskatchewan, Saskatoon, Saskatchewan, CanadaAbstract: For many years, central dogma defined multiple sclerosis (MS) as a T cell-driven autoimmune disorder; however, over the past decade there has been a burgeoning recognition that B cells contribute to the pathogenesis of certain MS disease subtypes. B cells may contribute to MS pathogenesis through production of autoantibodies (or antibodies directed at foreign bodies, which unfortunately cross-react with self-antigens), through promotion of T cell activation via antigen presentation, or through production of cytokines. This review highlights evidence for antibody-dependent and antibody-independent B cell involvement in MS pathogenesis.Keywords: autoantibodies, antibody targets, clinically isolated MS, primary progressive MS, secondary progressive MS, relapsing and remitting MS, T cells, T regulatory cells